Authority Delegation is a pathway in Enhancing Confidence between Directors and Employees in DAL Group in Khartoum North, Sudan - Ashraf A. Ahmed Hassan; Manal Hussain Mohammed Eltigani; Gaafar B. Suliman; Maruod E. Maruod (IJRDO - Journal of Social Science and Humanities Research, 2020)
The current study was conducted in DAL group in Khartoun North covering the period 2015-2018. The objectives of the study were to assess the role of authority delegation in enhancing the mutual confidence between the employees and the managers. Reveal the effect of authority delegation in employees self confidence. Primary data were collected via constructed questionnaire covering 105 DAL group directors and employees selected randomly. Descriptive statistics was used to analyze collected data.The results revealed that authority delegation Enhanced the confidence between directors and employees in DAL group, 58.0 % of the respondents were deeply agreed that there were good relationship between the employees and the directors, 42.0 % were agreed. 52.0 % of the respondents were strongly agreed that their relationships was good with the employees, 21.0 % were agreed.79.0 % of the respondents were strongly agreed that they do their work confidently due to authority delegation, 21.0 % were agreed. 76.0 % of respondents were strongly agreed that authority delegation lead to the belonging to the group. 37.0 % of the respondents agreed that they contributed with their manager in taking decisions, 42.0 % were agreed. Correlation Analysis results showed strong correlation between authority delegation and the existence of confidence between the employees and managers. It proved statistical indicator between authority delegation and the mutual confidence between directors and employees, and employees self confidence between the employees and managers. Study recommended more authority delegation for more confidence.